Une « histoire du féminisme latino-américain depuis une position subalterne ». Entretien avec Y. Espinosa-Miñoso - Espinosa-Miñoso, Yuderkys (CONTRETEMPS, 2019)
Yuderkys Espinosa-Miñoso est une penseuse, écrivaine, chercheuse, enseignante et activiste féministe antiraciste et décoloniale d’origine afrodominicaine. Elle prépare un doctorat en philosophie à l’Université de Buenos Aires sur la “critique de la raison féministe latinoamericaine” sous la direction de Maria Lugones. Elle est membre fondatrice du Groupe Latino-américain d’Etude, de Formation et d’Action Féministe (GLEFAS).
Keywords: LGBTQIA2+; afro-féminisme; antiracisme; approches et analyses; cours; discipline; féminisme afrocarabéen; féminisme décolonial; féminisme latinoaméricain; histoire et politique; intersectionnalité; militance; philosophie; pol4212; premier cycle; sciences humaines; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles